PRACTICE OF CREDITATION TO SMALL BUSINESSES BY COMMERCIAL BANKS OF THE REPUBLIC OF UZBEKISTAN - Olimova Muxlisa Vohidjon qizi (American Journals, 2024)
The practice of lending to small businesses by commercial banks of the Republic of Uzbekistan was analyzed. The structure of state support for lending to small businesses by banks in our country was considered.
Keywords: Small business, banking sector, banking system, basic accounting, international standard.